Justice, Anger and Wrath: Tracing the Im/Moral Dimensions of Payback - Celia E. Deane-Drummond (Religions, 2019)
Martha Nussbaum’s Anger and Forgiveness makes explicit claims about the moral valence and irrationality of the desire for payback. This article explores the roots of that desire through an analysis of research on inequity aversion in primates, and the sociocultural developmental context for expressions of anger. It explores the content of different expressions of anger and their relationship to rationality by engaging in the work of Thomas Aquinas. I argue that the desire for payback has biosocial roots in cooperation, and that these habits are prerequisites for the development of human moral sensibilities. However, the explicit desire for payback, like anger in general, is morally ambiguous. Anger may be laudable insofar as it is tied to constructive efforts, but the desire to see another person suffer is in itself morally repugnant. Christian religious interpretations of payback further complicate the narrative, since unappealing instances of this desire are thought by some Christians to be nonetheless justified under the banner of God’s wrath.